Synthesis and characterization of CoCrxFe2-xO4 nanoparticles - Hankare, P. P.; Sankpal, U. B.; Patil, R. P.; Mulla, Imtiaz S.; Lokhande, P. D.; Gajbhiye, N. S. (Journal of Alloys and Compounds, 2009)
Spinel-phase nanocrystalline CoCrxFe2-xO4 powders (0.0 <= x <= 2.0) were synthesized by citrate-gel precursor method. The samples were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM). transmission electron microscopy (TEM) and infra-red spectroscopy (FT-IR). The XRD and selected-area electron diffraction (SAED) patterns indicated that the synthesized nanoparticles have single-phase spinet structure without the presence of any other impurities. The changes in electrical and magnetic properties of different stiochiometric compositions have also been investigated. It is seen that with increase in chromium contents, the measured magnetic hysteresis loops become narrow with decreasing trend in saturation magnetization. Electrical resistivity indicated that all the compounds are semiconducting nature. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Magnetic measurements; Sintering; transmission electron microscopy; X-ray diffraction